Finite Element Model of Shape Memory Alloy Incorporating Drucker-Prager Model - Yan Tingjun; Zhao Linna (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
The unique features of shape memory alloys (SMA), including pseudoelasticity and shape memory effect, give SMAs a wide application in aeronautical, biomedical, and structural engineering. These features stimulate the interest in the development of constitutive models.  In this paper, a 3D finite element model of shape memory alloy material model has been developed to incorporate the Drucker – Prager model in order to describe the asymmetry of SMA under tension and compression. This paper also takes into account the variation of Young’s modulus of the austenite and the martensite.  The development and implementation of a robust integration algorithm is presented. The provided numerical simulation demonstrates its capabilities. Further studies should be performed to seek quantitative fitting with experimental results. DOI: http://dx.doi.org/10.11591/telkomnika.v11i7.2841